Validation of the Ottawa Ankle Rules: Strategies for Increasing Specificity - Morais, B (2022)
Introduction: The majority of patients with ankle injuries undergo radiological examinations of the foot, ankle or both. The objective of this study was in the first place to validate the Ottawa Ankle Rules (OARs) for the population of our centre. Secondly, an attempt was made to identify parameters that contribute to improve the specificity of the method, with a view to reduce the need for patients to be exposed to radiation as well as optimizing the expenses of the Emergency Ward (EW). Materials and methods: This was a prospective study conducted during a 9-month period. The study population included 148 patients, in 54 (36%) of the patients a fracture was present on the exams performed. Patients were submitted to a sequential protocol in the EW with a form completion, evaluation of OARs, application of the Visual Analog Pain Scale (VAS) and radiographic exams. Results: We found a sensitivity of OARs in ankle injuries of 100%, specificity of 26% and in midfoot injuries of 100% and 62% respectively. All patients with fractures had a VAS of 5 or more points in any of the tested sites. With the VAS criterium, we found a significant increase of global specificity (38% vs 15%), as well as when applied only to the ankle (26% to 47%) or to midfoot trauma (62% to 67%). In both, there would have been a 100% reduction of CT scans. Patients with a fracture or with fractures who required surgical treatment had a mean VAS significantly higher than patients with no fracture or fractures submitted to conservative treatment respectively. Although there was a lower percentage of fractures in the group of injuries in Work Accidents (31% vs 37% Sports Activity and 38% Leisure Activity), there was a statistically significant increase in the sum of average VAS in Accidents at Work vs Leisure Activities and vs Sports Activities. Conclusion: We seek to confirm the usefulness of OARs for our population and we investigated strategies to further reduce the need for unnecessary radiographs. The introduction of parameters for grading pain and adapting to the context of the accident seem promising